Economics and Psychology. The Framing of Decisions - SCHILIRO, Daniele (Journal of Mathematical Economics and Finance; Vol 2 No 2 (2016): JMEF Volume II, Issue 2(3), Winter 2016, 2017)
In the Theory of Rational Decision Making the psychological aspects are set aside. This contribution seeks to point out the relevance of psychology into eco- nomic decisions. The essay treats the “framing of decisions”, which is a pillar of Kahneman’s behavioral theory. Framing must be considered a special case of the more general phenomenon of dependency from the representation. The best-known risky choice-framing problem, i.e. the “Asian Disease Problem”, is shown where an essen- tial aspect of rationality: invariance, is violated. In addition, the contribution ex- plains Kahneman and Tversky’s Prospect Theory and illustrates their value function. Finally, it discusses the reversals of preference in framing and framing of contingen- cies. The framing manipulation is viewed as a public tool for influencing the decision maker’s private framing of the problem in terms of gains or losses, which determines the decision maker’s evaluation of the options. In conclusion, the psychology of choice is relevant both for the descriptive question of how decisions are made and for the nor- mative question of how decisions ought to be made.